2017
DOI: 10.3144/expresspolymlett.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of imidazolium-based poly (ionic liquid) assemblies during solvent evaporation

et al.

Abstract: The fabrication of polymer-based assemblies with molecular packing at different length scales has recently received a great deal of attention due to their promising potentials to produce functional, nanostructured materials [1][2][3][4][5]. Amphiphilic block or graft copolymers are common candidates for such self-assembled organization and ordering in nano-, and mesoscale. This self-assembly behavior is normally driven by a variety of covalent interaction and noncovalent interactions (e.g., electrostatics, hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…As shown in Figure b, P­[STFSI]­[N1111] displays one broad amorphous peak at 17.0° and a sharp XRD peak at 5.4°. The sharp peak indicates that there is an increase of interplanar and intraplanar ordered packing of P­[STFSI] + chains or semicrystalline structure in P­[STFSI]­[N1111] as shown by the bottom inset in Figure b. , P­[STFSI]­[N2222] only displays one broad peak at 15.2°, indicating a relatively uniform amorphous structure as shown by the middle inset in Figure b . P­[STFSI]­[N3333] displays two broad peaks at 11.3° and 20.9°.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As shown in Figure b, P­[STFSI]­[N1111] displays one broad amorphous peak at 17.0° and a sharp XRD peak at 5.4°. The sharp peak indicates that there is an increase of interplanar and intraplanar ordered packing of P­[STFSI] + chains or semicrystalline structure in P­[STFSI]­[N1111] as shown by the bottom inset in Figure b. , P­[STFSI]­[N2222] only displays one broad peak at 15.2°, indicating a relatively uniform amorphous structure as shown by the middle inset in Figure b . P­[STFSI]­[N3333] displays two broad peaks at 11.3° and 20.9°.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Several discernible peaks provided evidence for an imidazolium ring, including N-H stretching at 3397.96 cm to the presence of alkyl chain groups. [42][43][44] Numerous earlier studies revealed that the absence of the C-Br stretching absorbance band in the IR spectra for the absorption of singleelement anions Br was caused by the synthesis of the imidazolium salt and the lack of bond vibration. [45][46][47]…”
Section: To Validate the Synthesis Of [Hmim][br] And [Omim]mentioning
confidence: 99%